Microstructures Changes in Aluminum 6061 Due To Oxidation before MMAW Welding - Anrinal Anrinal; Asmara Yanto; Rahmad Hidayat (LP2M - Institut Teknologi Padang, 2020)
This work aims to provide an overview of the changes in the microstructure of Aluminum 6061 because it was oxidized prior to MMAW welding. The research was conducted by first allowing aluminum 6061 to oxidize in the air (atmosphere) with a time variation of 0, 120, and 240 hours. The MMAW welding process uses a 1G welded seam without a 1G position, Grilumin 14 electrode, AWS A5.3-99 specifications, E4043 3.2 mm in diameter, with a DC current of 90 Amperes. The welding results show that the weld surface appears sooty and rough spots where the longer the oxidation occurs produces more soot and spots, while the results of the microstructure examination on the weld area and the HAZ area show that the micro structure of the weld area and the HAZ area experiences increased grain size.